Conduct disorder in girls: neighborhoods, family characteristics, and parenting behaviors - Chang Chien-Ni; Tritt Karin; Stein Stefanie; Pajer Kathleen; Wang Wei; Gardner William (BMC, 2008)
Abstract Background Little is known about the social context of girls with conduct disorder (CD), a question of increasing importance to clinicians and researchers. The purpose of this study was to examine the associations between three social context domains (neighborhood, family characteristics, and parenting behaviors) and CD in adolescent girls, additionally testing for race moderation effects. We predicted that disadvantaged neighborhoods, family characteristics such as parental marital status, and parenting behaviors such as negative discipline would characterize girls with CD. We also hypothesized that parenting behaviors would mediate the associations between neighborhood and family characteristics and CD. Methods We recruited 93 15-17 year-old girls from the community and used a structured psychiatric interview to assign participants to a CD group (n = 52) or a demographically matched group with no psychiatric disorder (n = 41). Each girl and parent also filled out questionnaires about neighborhood, family characteristics, and parenting behaviors. Results Neighborhood quality was not associated with CD in girls. Some family characteristics (parental antisociality) and parenting behaviors (levels of family activities and negative discipline) were characteristic of girls with CD, but notll. There was no moderation by race. Our hypothesis that the association between family characteristics and CD would be mediated by parenting behaviors was not supported. Conclusion This study expanded upon previous research by investigating multiple social context domains in girls with CD and by selecting a comparison group who were not different in age, social class, or race. When these factors are thus controlled, CD in adolescent girls is not significantly associated with neighborhood, but is associated with some family characteristics and some types of parental behaviors. However, the mechanisms underlying these relationships need to be further investigated. We discuss possible explanations for our findings and suggest directions for future research.